University entrepreneurship in the face of the Covid-19 pandemic: The example of the Universidade Federal do Rio Grande do Sul (Research, Society and Development, 2023)
This study aims to identify, index, classify and quantify the entrepreneurial actions carried out within the scope of a federal university in reaction to the start of the Covid-19 pandemic, selected based on the criterion of having been published as news on this institution's website, the Universidade Federal do Rio Grande do Sul (UFRGS). Related to the Entrepreneurial University research line, it identifies these entrepreneurial actions using the value creation criterion and classifies them according to evaluation indicators from this line, also observing the participation of the areas of knowledge and the entrepreneurship system of that institution in the initiatives. Using the quantitative method, it was found that all areas of knowledge, according to the categorization of the Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq), carried out entrepreneurial actions, with a preponderance of Health Sciences, followed by the areas of Applied Social Sciences and Exact and Earth Sciences. Among the indicators that evaluate university entrepreneurship in Brazil, proposed by the Confederação Brasileira de Empresas Juniores (Brasil Júnior), the entrepreneurial actions cataloged were predominantly classified in the “Extension” and “Innovation” axes. In relation to the participation of the UFRGS entrepreneurship system, it had an impact on 10% of the actions. The sample collected indicates that there was a more immediate response time in the first month of the pandemic, and a decrease in the number of new entrepreneurial actions in the subsequent two months. Considers that this university presented a diverse reaction to the global health crisis, interacting with each other and with society for its development. It also considers that the parameters used (response time, participation in the entrepreneurship system, frequency in relation to university entrepreneurship axes and in relation to areas of knowledge) can be applied in assessments of reactivity to the pandemic in other universities.